The Relationship Of Static Work Toward Muscle Fatigue And Fatigue Recovery Rate - Harun, Azimah (Universiti Sains Malaysia, 2006)
The aim of this study was to find the relationship of the static work toward muscle fatigue and fatigue recovery time. The healthy subjects of nine male and ten female subjects (age: 22-25 years, height: 1.48-1.79 m, weight: 36-75 kg) are exercised on a static work task which is hanging the different of work loads with to their wrist condition level, elbow condition level, and shoulder condition level.. The result of the study show that, (1) the relationship between the load, time to fatigue, relative heart rate, relative systolic, and relative diastolic, (2) the significant correlation value between each item (load, time to fatigue, RHR, RSYS, and RDIAS), (3) the trend of the graph between the relationship variables. The relationships for these items are linear relation (direct or inverse relation). That means, when the load is increase, the relative heart rate is increase too. For the time to fatigue, it is show the strongly relationship and the relationship is inverse relation with the load that means when the load increasing, hence the time to become fatigue is rapidly decrease.